Plasma‐Enhanced Magnetron Sputtering: A Novel Approach for Biofunctional Metal Nanoparticle Coatings on Reverse Osmosis Composite Membranes - Nicole Michler; Ulrike M. Hirsch; Carolin Steinert; Gregor Fritzsche; Christian E. H. Schmelzer (Advanced Materials Interfaces)
Abstract Reverse osmosis (RO) is the most common method for treating salt and brackish water. As a membrane‐driven process, a key challenge for RO systems is their susceptibility to scaling and biofouling. To address these issues, functional coatings utilizing metal nanoparticles (MNPs) are developed. In this study, silver, gold, and copper nanoparticles are applied onto thin‐film composite (TFC) membranes using plasma‐enhanced magnetron sputtering. The elemental composition, surface morphology, and hydrophilicity of the coatings are analyzed using X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and contact angle measurements. The antimicrobial properties and the filtration efficiency of the coated membranes are assessed through application‐specific experimental setups. Silver and copper nanoparticles exhibit superior antimicrobial properties, reducing microorganism adhesion by a factor of 103 compared to uncoated membranes. Under appropriate coating conditions, no deterioration in filtration performance is observed. Enhancing the adhesion of MNPs is necessary for achieving sustained release of metal ions.